Crime risk and housing values: evidence from the gun offender registry - Tang, Cheng Keat (2023)
This paper estimates the effects of crime risk on housing values. To estimate the causal effects, we rely on the introduction of the gun offender registry in Baltimore City, Maryland, that discloses the residences of ex-gun offenders to the public. Specifically, we exploit the changes in perceived crime risk after ex-gun offenders move into the neighborhoods. Our most conservative estimates indicate that houses within 0.1 miles from ex-gun offenders’ residences experience an 8.0% decline in value ($12,632) after these ex-gun offenders move in. Additional results suggest that homeowners are responding out of fear of victimization as we do not observe significant increases in crimes following the relocation of ex-gun offenders into the neighborhoods.